2022
DOI: 10.1002/puh2.17
|View full text |Cite
|
Sign up to set email alerts
|

Towards a post‐COVID world: Challenges and progress of recovery in Kazakhstan

Abstract: Kazakhstan announced the first cases of COVID‐19 in March 2020. Within a span of a few months, the pandemic ravaged all regions affecting vulnerable populations due to limited access to healthcare services and co‐morbidities. To minimize the spread of the pandemic, the government announced the implementation of containment measures such as quarantine, movement restrictions, and lockdowns among others. The collateral effect of the pandemic has disrupted economic and learning activities pushing several people be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…There is a scarcity of scientific literature on the impact of limited access to healthcare on one's psychological health during the pandemic in Kazakhstan. Nevertheless, the available sources suggest that Kazakhstan had a number of challenges prior to COVID-19 such as shortage in healthcare funding, high prevalence of chronic diseases, and limited access to medical care (Haruna et al, 2022). The One source suggests that the depressed salary among the healthcare staff to be one of the driving reasons for having low numbers of medical personnel in the country (Kumenov, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is a scarcity of scientific literature on the impact of limited access to healthcare on one's psychological health during the pandemic in Kazakhstan. Nevertheless, the available sources suggest that Kazakhstan had a number of challenges prior to COVID-19 such as shortage in healthcare funding, high prevalence of chronic diseases, and limited access to medical care (Haruna et al, 2022). The One source suggests that the depressed salary among the healthcare staff to be one of the driving reasons for having low numbers of medical personnel in the country (Kumenov, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In response to the pandemic, healthcare professionals have made a commitment to the service of others despite the impact on their emotional and physical wellbeing due to insecurities, differing work demands and increased work hours. [33][34][35] Moreover, significant amounts of variance in work may indirectly create a considerable amount of anxiety and stress among medical staff. 16 36 However, the pandemic has brought a risk of infection and a high mortality rate as well as psychological and mental trauma to the public and medical personnel.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…56 An international study 57 was conducted among 904 nurses across Japan, the Republic of Korea, the Republic of Turkey and the USA. It stated that CD-RISC-10 scores can be categorised as low (0-10), intermediate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Similarly, it was reported that an overall CD-RISC range=35.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…6 While these vaccines are the cornerstone for COVID-19 pandemic mitigation, a strategy for fair global distribution that reduces vaccine wastage is crucial for maximising the effects of vaccination. 7 Though COVID-19 vaccines have been made available for more than a year, only about 21.2% of the African population have received the recommended doses of the vaccine, with Nigerians accounting for 13.8% as of August 2022 and yet unneeded vaccine wastage is still occurring. 8 Therefore, there is an urgent need for plans in Nigeria to monitor, forecast, and ultimately reduce vaccine wastage.…”
Section: Introductionmentioning
confidence: 99%